A Single Step Synthesis of Substituted 3,7-Dimethyl-5-nitro-4H-1,4-benzothiazines - Adwani, Purnima; Mathur, Neha; Gupta, Vandana; Ojha, K.G. (Asian Journal of Chemistry, 2010)
In this communication, the authors report the synthesis of substituted 3,7 -dimethyl-5-nitro-4H -1 ,4-benzothiazines.